2018
DOI: 10.21512/lc.v12i4.4118
|View full text |Cite
|
Sign up to set email alerts
|

Directive Speech Acts and Hedges Presented by Female Main Characters of Jane Austen’s Novels

Abstract: This research aimed at identifying the category of directive speech acts found in the utterances of six female characters of six Jane Austen’s novels (Elinor Dashwood of Sense and Sensibility, Elizabeth Bennet of Pride and Prejudice, Fanny Price of Mansfield Park, Emma Woodhouse of Emma, Anne Elliot of Persuasion, and Catherine Morland of Northanger Abbey), and explaining the hedges used in directive speech acts. The research employed a descriptive qualitative method to collect, analyze, and discuss the findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The factor of directive speech cat can be segregated into different categories that tends to follow ask, order, request, command begging permitting and so on. In case of the character promoted by Jane Austen asking, advising and requesting are important direct speech characteristics observed [3]. Such characteristics are signifying classical etiquettes carried by contemporary female audiences belonging from the British countryside.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The factor of directive speech cat can be segregated into different categories that tends to follow ask, order, request, command begging permitting and so on. In case of the character promoted by Jane Austen asking, advising and requesting are important direct speech characteristics observed [3]. Such characteristics are signifying classical etiquettes carried by contemporary female audiences belonging from the British countryside.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The is in the form of translation techniques used in translating all of speech containing verbal abuse in the novel The Dark Heroine: Dinner With A Vampire. In addition, Searle (1981) classified speech acts into five categories (as cited in Suyavonika & Julhijah, 2018, p.346). These are assertive, expressive, declarative, expressive, and commissive.…”
Section: Verbal Abusementioning
confidence: 99%
“…Then, social class, the link between individuals, and formality also impact how directive forms are used. Suryanovika and Julhijah (2018) The findings showed that directive speech acts are formed imperatively, declaratively, and interrogatively. Meanwhile, Winarti, et al (2015), the result showed that direct or indirect directed speech acts can be heard in the Dolanan song.…”
Section: Introductionmentioning
confidence: 96%